2016
DOI: 10.3847/1538-4357/833/2/193
|View full text |Cite
|
Sign up to set email alerts
|

YOUNG STELLAR POPULATIONS IN MYStIX STAR-FORMING REGIONS: CANDIDATE PROTOSTARS

Abstract: The Massive Young Star Forming Complex in Infrared and X-ray (MYStIX) project provides a new census on stellar members of massive star forming regions within 4 kpc. Here the MYStIX Infrared Excess catalog (MIRES) and Chandra-based X-ray photometric catalogs are mined to obtain high-quality samples of Class I protostars using criteria designed to reduce extragalactic and Galactic field star contamination. A total of 1,109 MYStIX Candidate Protostars (MCPs) are found in 14 star forming regions. Most are selected… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 187 publications
(161 reference statements)
0
12
0
Order By: Relevance
“…Our follow-up study found a rich group of 24 candidate Class 0/I protostars in the region 09 h 01 m 12 s < α < 09 • 02 24 and -47:40< δ <-47:45 (Romine et al 2016). They lie along a dusty filament seen in Herschel infrared maps that is oriented northwest to southeast, bifurcated by the older IRAS 09002-4732 star cluster.…”
Section: Introduction 1the Formation Of Star Clustersmentioning
confidence: 70%
“…Our follow-up study found a rich group of 24 candidate Class 0/I protostars in the region 09 h 01 m 12 s < α < 09 • 02 24 and -47:40< δ <-47:45 (Romine et al 2016). They lie along a dusty filament seen in Herschel infrared maps that is oriented northwest to southeast, bifurcated by the older IRAS 09002-4732 star cluster.…”
Section: Introduction 1the Formation Of Star Clustersmentioning
confidence: 70%
“…This is not surprising, given that no large H II region is present in DR21 (Figure 2h), and the most luminous IR point sources are protostars and pre-main sequence stars with dusty disks Romine et al 2016). Bright, extended MIR emission associated with embedded massive stars also foils the MYStIX MIR point-source photometry.…”
Section: A4 Dr 21mentioning
confidence: 99%
“…Complementary to the MYStIX sample of >30,000 probable cluster members , Romine et al (2016) provide the catalog of >1000 MYStIX candidate ClassI protostars. The science studies on stellar mass segregation (M. A.…”
Section: Mystix As a Foundation For Sfincsmentioning
confidence: 99%
“…Since the J−H color is also a surrogate for spectral type, its values for many known lightly/moderately absorbed OB-type members are shifted downwards with respect to the PMS locus. In their MYStIX science study of new protostellar objects in the MYStIX regions, Romine et al (2016) usedX-ray median energy >4.5 keV as a strict criterion to discriminate ClassI protostars from ClassII-III systems.…”
Section: Global Properties Of Spcmsmentioning
confidence: 99%